Analysis of Ansy Lema's Reses Fund Usage Report on Instagram Social Media: Principal-Agent Perspective - Antonius Jefrino Fahik (Green Publisher Indonesia, 2024)
This article analyzes the use of recess funds reported by Ansy Lema on his personal Instagram social media account. The research object is analyzed using the principal-agent theory. Using a descriptive-qualitative approach, data collection strategies were conducted through textual observation techniques on Ansy Lema's Instagram pages. From a principal-agent perspective, what Ansy Lema uploads on Instagram reflects aspects of transparency, accountability, and independence as a representative of the people. This affirms that Ansy Lema can be responsible, honest, and have integrity. Through these uploads, the public can communicate more openly with their representatives, not only to express appreciation but also to criticize and evaluate their political policies. This article contributes in two ways. First, theoretically, it supports the idea that in the context of a digital society, social media can serve as a medium for politicians to work more transparently, accountably, and with integrity. Second, Instagram can serve as a means to minimize free riders in democracy by encouraging the democratic political communication between the people (principal) and their representatives (agent).